Combating plastic and marine ecosystems. The legal framework arising from Directive (EU) No 2019/904 - Belviso, Luca (Przegląd Prawa Rolnego, 2019)
The article describes, first, the global emergency related to the production, consumption and dispersion in the environment of non-recyclable or reusable disposable plastic. Subsequently, it continues with the analysis of the objectives and measures established in the context of the European strategy for plastics and the recent Directive(EU) No 2019/904. In fact, behind the objectives and legal solutions offered by the European Union, there is the hope, shared by the author, that the challenges connected to the production, consumption and the end of the life cycle of plastic can become opportunities, and will not only guarantee everyone a healthier environment, but will also drive the European plastics industry towards innovation and growth, creating at the same workplaces and increasing the rate of employment.